Combination Treatment with the GSK-3 Inhibitor 9-ING-41 and CCNU Cures Orthotopic Chemoresistant Glioblastoma in Patient-Derived Xenograft Models - Ugolkov, A.; Qiang, W.; Bondarenko, G.; Procissi, D.; Gaisina, I.; James, C.; Chandler, J.; Kozikowski, A.; Gunosewoyo, Hendra; O'Halloran, T.; Raizer, J.; Mazar, A. (2017)
Resistance to chemotherapy remains a major challenge in the treatment of human glioblastoma (GBM). Glycogen synthase kinase-3ß (GSK-3ß), a positive regulator of NF-?B–mediated survival and chemoresistance of cancer cells, has been identified as a potential therapeutic target in human GBM. Our objective was to determine the antitumor effect of GSK-3 inhibitor 9-ING-41 in combination with chemotherapy in patient-derived xenograft (PDX) models of human GBM. We utilized chemoresistant PDX models of GBM, GBM6 and GBM12, to study the effect of 9-ING-41 used alone and in combination with chemotherapy on tumor progression and survival. GBM6 and GBM12 were transfected by reporter constructs to enable bioluminescence imaging, which was used to stage animals prior to treatment and to follow intracranial GBM tumor growth. Immunohistochemical staining, apoptosis assay, and immunoblotting were used to assess the expression of GSK-3ß and the effects of treatment in these models. We found that 9-ING-41 significantly enhanced 1-(2-chloroethyl)-3-cyclohexyl-1-nitrosourea (CCNU) antitumor activity in staged orthotopic GBM12 (no response to CCNU) and GBM6 (partial response to CCNU) PDX models, as indicated by a decrease in tumor bioluminescence in mouse brain and a significant increase in overall survival. Treatment with the combination of CCNU and 9-ING-41 resulted in histologically confirmed cures in these studies. Our results demonstrate that the GSK-3 inhibitor 9-ING-41, a clinical candidate currently in Investigational New Drug (IND)-enabling development, significantly enhances the efficacy of CCNU therapy for human GBM and warrants consideratio n for clinical evaluation in this difficult-to-treat patient population.